Adjuvant therapy following resection of gastroenteropancreatic neuroendocrine tumors provides no recurrence or survival benefit. Issue 7 (9th March 2020) - Barrett, James R.; Rendell, Victoria; Pokrzywa, Courtney; Lopez‐Aguiar, Alexandra G.; Cannon, John; Poultsides, George A.; Rocha, Flavio; Crown, Angelena; Beal, Eliza; Michael Pawlik, Timothy; Fields, Ryan; Panni, Roheena Z.; et al.
Abstract: Background and Objectives: Lack of high‐level evidence supporting adjuvant therapy for patients with resected gastroenteropancreatic neuroendocrine tumors (GEP NETs) warrants an evaluation of its non‐standard of care use. Methods: Patients with primary GEP NETs who underwent curative‐intent resection at eight institutions between 2000 and 2016 were identified; 91 patients received adjuvant therapy. Recurrence‐free survival (RFS) and overall survival (OS) were compared between adjuvant cytotoxic chemotherapy and somatostatin analog cohorts. Results: In resected patients, 33 received cytotoxic chemotherapy, and 58 received somatostatin analogs. Five‐year RFS/OS was 49% and 83%, respectively. Cytotoxic chemotherapy RFS/OS was 36% and 61%, respectively, lower than the no therapy cohort ( P  < .01). RFS with somatostatin analog therapy (compared to none) was lower ( P  < .01), as was OS ( P  = .01). On multivariable analysis, adjuvant cytotoxic therapy was negatively associated with RFS but not OS controlling for patient/tumor‐specific characteristics (RFS P  < .01). Conclusions: Our data, reflecting the largest reported experience to date, demonstrate that adjuvant therapy for resected GEP NETs is negatively associated with RFS and confers no OS benefit. Selection bias enriching our treatment cohort for individuals with unmeasured high‐risk characteristics likely explains some of these results; future studies should focus on patient subsets who may benefit from adjuvant therapy.